Quantification of genetic variation on Island-breeding populations of Procellariiformes : an assessment of the impact of the longline fishing industry on seabirds - Kelso, Janet (University of Cape Town, 2000)
Bibliography: p. 83-94. The number of albatrosses that are killed on longlines in the Southern ocean is conservatively estimated to be 44 000 birds per annum. These numbers are biologically significant since albatrosses are a prime example of an extreme K-selected species. Ongoing long line fishing in the Southern ocean could lead to a decrease in the size of breeding colonies, and is a cause for major concern as it may impact the long-term survival of these birds. Quantifying genetic variation in threatened populations is a valuable application of molecular biology in conservation. In this study genetic variation was quantified using microsatellite analysis in order to investigate the effects of the longline fisheries on seabird populations. In addition, the feasibility of developing diagnostic markers for determining the provenance of birds forming part of the bycatch was also investigated. The inter-population genetic variance of three species of albatross from four distinct breeding colonies is described. Microsatellite markers were found to be highly variable and provided an assessment of the heterzygosity in the distinct populations, and a measure of the gene flow between these populations. Despite the extreme fidelity that adult albatrosses show to their breeding colonies, relatively low levels of genetic differentiation were observed between the colonies. This suggests that an integrated conservation management strategy could be undertaken successfully.